(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The article is devoted to the analysis of the concept of Neuro-Linguistic Programming (NLP) as a methodology aimed at enhancing communication effectiveness, developing personal and professional skills, and forming stable behavioral strategies in various life and professional situations. The key principles of NLP are considered, including the interconnection of thinking, language, and behavior, as well as methods for modeling successful experiences. The article emphasizes the practical application of NLP in pedagogy, psychology, business, and personal development, which allows optimizing learning processes, communication, and self-regulation. The article is intended for specialists in pedagogy, psychology, management, and anyone interested in methods for improving personal effectiveness and professional competencies.